Analysis of frailty syndrome in primary care - Cross sectional study - Augusti, Ana Carolina Veloso (2017)
Objective: To assess the prevalence of frailty syndrome in elderly patients in primary health care. Methods: A cross-sectional study that included a sample of 306 individuals of both sexes, aged 65 years or older, living in the neighborhood of Jardim Camanducaia, city of Amparo, SP, Brazil. We evaluated data on sex, age, chronic disease, cognitive performance, and the phenotype of frailty, which considered grip strength, gait speed, level of physical activity, weight loss and fatigue. Results: It was found a predominance of females (60%) in the sample. 21.5% of the studied patients were characterized as frail, 71.5% of elderly people have been classified as pre-frail, and 6% of the sample were categorized as non-frail. Conclusion: There was a high prevalence of frail and pre-frail elderly patients, and this finding points to the need for periodic evaluation of the elderly by a multidisciplinary team. Thus, frailty could be prevented, in order to reduce or minimize adverse outcomes concerning health.